(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the efficacy of wide bore tube in vesicovaginal fistula repair for urinary drainage. Study Design: Observational / descriptive / cross sectional study. Place and Duration of Study: This study was carried out in the Department of Gynae & Obs at Medical College/District Headquarter Hospital Mirpur Azad Kashmir from May 2009 to July 2012. Materials and Methods: All the patients were evaluated with history, physical examination and required labs. Cystoscopy was done in all patients before surgery. Repair was done in two layers. Bladder was drained with 20fr open end drain for first 72 hours, which was replaced with Foley catheter. Results: Total 28 patients with mean age 31 years (18-49 yrs), twenty three (82.1%) patients were having primary fistula while five (17.9%) had undergone surgical repair before. Location of fistulas were trigonal in 20 (71.4%) patients, supra trigonal 6 (21.4%) patients and 2 (7.1%) were involving the urethra. Twenty one (75%) patients were managed through vaginal route which include both trigonal and supra trigonal fistulas, remaining 7 (25%) repairs were done through the abdominal route. In twenty seven (96.4%) patients the repair was successful on removal of catheter. Conclusion: Approach for repair of VVF depends upon the preference and experience of surgeon. Success rate can be improved by following basic principles and good urinary drainage with drain.